The isolation and characterization of bacteriophage T7 messenger RNA fragments containing an RNase III cleavage site. - Kramer, R A (Nucleic Acids Res, 1976)
We have isolated overlapping RNA fragments which contain the region surrounding the ribonuclease III cleavage site between bacteriophage T7 genes 0.3 and 0.7. Although all of these fragments contain the site of cleavage, only certain fragments are correctly recognized and cleaved by RNase III. Analysis of the cleavage products of the fragments indicates that the enzyme produces a single endonucleolytic break at this site in the T7 early RNA precursor molecule. In addition, the 3'-terminal adenylic acid residues observed previously on the in vivo T7 early RNA species were not found in these fragments and, therefore, must represent a post-transcriptional, post-processing modification of the RNA. IMAGES: